2008
DOI: 10.1364/ao.47.006385
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of electromagnetic waves in Kolmogorov and non-Kolmogorov atmospheric turbulence: three-layer altitude model

Abstract: Turbulence properties of communication links (optical and microwave) in terms of log-amplitude variance are studied on the basis of a three-layer model of refractive index fluctuation spectrum in the free atmosphere. We suggest a model of turbulence spectra (Kolmogorov and non-Kolmogorov) changing with altitude on the basis of obtained experimental and theoretical data for turbulence profile in the troposphere and lower stratosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 24 publications
1
71
0
1
Order By: Relevance
“…(5)- (8) arbitrary moment radius of HermiteGaussian beam can be derived. In general, the spatial power spectrum is written as [11,16] …”
Section: Formulation For Arbitrary Moment Radius Of Hermite-gaussian mentioning
confidence: 99%
See 2 more Smart Citations
“…(5)- (8) arbitrary moment radius of HermiteGaussian beam can be derived. In general, the spatial power spectrum is written as [11,16] …”
Section: Formulation For Arbitrary Moment Radius Of Hermite-gaussian mentioning
confidence: 99%
“…/ 4π 2 is a constant that maintains consistency between the index structure function and its power spectrum [9,11,16], β is the general refractive index structure constant and has the units of…”
Section: Formulation For Arbitrary Moment Radius Of Hermite-gaussian mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Kolmogorov spectrum is only effective in inertial subrange. In last several decades, it has been experimentally indicated that turbulence in the upper troposphere and stratosphere deviates from predictions of the Kolmogorov model [2,3], and in the case of laser propagation along the vertical direction, the turbulence is no longer homogeneous in three dimensions, since the vertical component is suppressed [4]. Taking into account the slope variation of the atmospheric power spectrum, Toselli et al introduced a non-Kolmogorov power spectrum [5,6] by using a generalized exponent and a generalized amplitude factor instead of a constant standard exponent value 11/3 and a constant value 0.033 associated with the conventional Kolmogorov power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…For the propagation along the slant path, the turbulence shows non-Kolmogorov characters, and its spectral exponent depends strongly on the altitude [5]. It can be understood by the mechanisms of turbulent generation and dissipation being different at high and low altitudes, which results in the difference in turbulent spectra [6].…”
mentioning
confidence: 99%